The First Stone and the Last Tasmanian: The Colonial Correspondence of Edward Burnett Tylor and Henry Ling Roth. Issue 3 (28th October 2016) - Taylor, Rebe
Abstract : Between 1890 and 1905, Edward Burnett Tylor and Henry Ling Roth extended and formalised two ideas that were intricately connected and deeply influential to the development of nineteenth century anthropology: that the Tasmanian Aboriginal people represented the earliest phase of cultural evolution and that they were extinct. This paper offers a detailed archival exploration of the correspondence between 1891–1905 that informed those ideas. It finds that Tylor and Roth not only received abstracted facts and artefacts from their colonial contacts; they were directed and inspired by an emergent Australian scholarship that sought to propose and urge new disciplinary directions. This paper reveals not only the importance of Tasmanian Aboriginal people to the history of science, but the role that scientific ideas have shaped Australian social memory and national identity.